Relationship between job satisfaction, burnout syndrome and depressive symptoms in physicians: a cross-sectional study based on the employment demand-control model using structural equation modelling - Villarreal-Zegarra, David (2022)
Objective To evaluate the relationship between job satisfaction, burnout syndrome (BS) and depressive symptoms (DS) based on the job demand-control framework model on a nationally representative sample of physicians working in the Peruvian Health System. Setting We carried out a secondary data analysis of the National Survey of Satisfaction of Users in Health 2016 in Peru. Primary and secondary outcome measures Our study assessed the development of the predictive model and had two parts: (1) to evaluate the association among the variables based on the job demand-control framework, and (2) to assess the proposed model acceptability using the structural equation modelling approach to estimate goodness-of-fit indices (GOFIs). Participants We excluded physicians older than 65 years, who did not report income levels or who had missing data related to the workplace. Thus, we analysed 2100 participants. Results The prevalence of DS was 3.3%. Physicians' work-related illnesses had more probability to result in DS (prevalence ratio=2.23). DS was moderately related to BS dimensions (r>0.50); nevertheless, the relationships between DS and the three job satisfaction scales were weak (r<0.30). The first predictive model based on the variables, DS, BS and job satisfaction, had low GOFIs (comparative fit index (CFI)=0.883; root mean square error of approximation (RMSEA)=0.125). In a second evaluation, we used models with correlated errors obtaining optimal GOFIs (CFI=0.974; RMSEA=0.060). Conclusions Our study identified a stable model to explain the relationship between job satisfaction, BS and DS among physicians. The results are consistent with the job demand-control framework. They could be applied to decision-making in occupational contexts in Latin American low/middle-income countries.